2018
DOI: 10.1093/cercor/bhy151
|View full text |Cite
|
Sign up to set email alerts
|

Mental Imagery Follows Similar Cortical Reorganization as Perception: Intra-Modal and Cross-Modal Plasticity in Congenitally Blind

Abstract: Cortical plasticity in congenitally blind individuals leads to cross-modal activation of the visual cortex and may lead to superior perceptual processing in the intact sensory domains. Although mental imagery is often defined as a quasi-perceptual experience, it is unknown whether it follows similar cortical reorganization as perception in blind individuals. In this study, we show that auditory versus tactile perception evokes similar intra-modal discriminative patterns in congenitally blind compared with sigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 143 publications
1
14
0
Order By: Relevance
“…In summary, our results provide evidence that prior information can drive somatotopic activity in early somatosensory areas even in the absence of tactile stimuli, and that this activity is task relevant. This findings adds to the recent literature which indicates that S1 is involved in higher order processing of tactile information [25,26,56] and that it does so by the exploitation of its somatotopic organization [56].…”
Section: Discussionsupporting
confidence: 76%
“…In summary, our results provide evidence that prior information can drive somatotopic activity in early somatosensory areas even in the absence of tactile stimuli, and that this activity is task relevant. This findings adds to the recent literature which indicates that S1 is involved in higher order processing of tactile information [25,26,56] and that it does so by the exploitation of its somatotopic organization [56].…”
Section: Discussionsupporting
confidence: 76%
“…The past decade has witnessed an explosion of interest in examining neural underpinnings of cross-modal plasticity following sensory loss (Borst and Gelder, 2018; Heimler et al., 2015; Singh et al., 2018). Although the existence of such cross-modal changes is certain, the properties of these cross-modal adaptations remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies [ 63 ] have suggested that pSTG was more involved in the sound localization, while aSTG was related to auditory pattern processing, which may be explained by anterior-posterior functional dissociation in temporal areas. The increase of pSTG might correspond to the improvement of the ability of the sound localization in EBAs, which might indicate that cortical plasticity following visual deprivation enhances intramodal organization of auditory and tactile perception [ 64 ].…”
Section: Discussionmentioning
confidence: 99%